Sausage`s consumer habits in two different geographical areas in Costa Rica - Araya-Quesada, Yorleny (2014)
Market research was conducted in two different geographical areas in Costa Rica: San Carlos and Metropolitan area in order to compare the consumer preferences about sausages. One mini group session with 5 persons and a group session with 9 persons were conducted in San Carlos. In the Metropolitan area, two mini groups session with 6 persons each also took place. A thematic analysis was applied. A questionnaire was designed using results from qualitative investigation. The survey was by telephone, the sample size was n=193. Survey data were analyzed using descriptive statistics and also to relate the results a chi-square ratio test (X2) was applied (5% significance). Not significant differences were found between people from the two geographical areas, except sausages preference in the Metropolitan area is ham and in San Carlos is saucisson. Consumers eat sausages because they have good taste and are convenient, are usually accompanied with cereals and vegetables.